Effects of oily fish intake on cardiometabolic markers in healthy 8- to 9-y-old children: the FiSK Junior randomized trial. Issue 6 (9th October 2019) - Vuholm, Stine; Rantanen, Jesper M; Teisen, Marie N; Stark, Ken D; Mølgaard, Christian; Christensen, Jeppe H; Lauritzen, Lotte; Damsgaard, Camilla T
ABSTRACT: Background: Fish oil improves cardiometabolic markers in adults, but results in children are inconsistent. Few children meet the recommended fish intake and no randomized trials have investigated how fish intake per se affects children's cardiometabolic profile. Objective: We investigated whether oily fish consumption modulated serum triacylglycerol and diastolic blood pressure (coprimary outcomes) and other cardiometabolic markers in healthy Danish children and whether effects were sex-specific. Methods: In a randomized controlled 12-wk trial, 199 children (aged 8–9 y) received ∼300 g/wk of oily fish or poultry (control). We measured blood pressure, heart rate, and heart rate variability (HRV) via 3-h continuous electrocardiograms and collected fasting blood samples for analysis of erythrocyte EPA [20:5n–3 (ω-3)] + DHA (22:6n–3) and serum triacylglycerol, LDL and HDL cholesterol, glucose, and insulin. Results: One hundred and ninety-seven children (99%) completed the trial. The fish group consumed a median (IQR) of 375 (325–426) g oily fish/wk and the poultry group consumed 400 (359–452) g poultry/wk, which resulted in 2.25 (95% CI: 1.88, 2.62) fatty acid percentage-point higher erythrocyte EPA + DHA in the fish group ( P  < 0.001). In the fish group, serum triacylglycerol decreased by 0.05 mmol/L (95% CI: 0.00, 0.11 mmol/L) ( P  = 0.04) and HDL cholesterol increased by 0.07 mmol/L (95% CI: 0.01, 0.13 mmol/L) ( P  = 0.02); the triacylglycerol effect showed dose-dependency with erythrocyte EPA + DHA ( r  = −0.15, P  = 0.04), whereas HDL showed a tendency for such an association( r  = 0.13, P  = 0.08). Additional analyses indicated sex-specificity ( P diet*sex  < 0.10), because triacylglycerol was reduced by 0.09 mmol/L (95% CI: 0.02, 0.16 mmol/L) in boys only (girls: −0.00; 95% CI: −0.07, 0.07 mmol/L) and heart rate was reduced by 3.4 bpm (95% CI: 0.2, 6.6 bpm) in girls only (boys: 0.6; 95% CI: −2.6, 3.8 bpm). Blood pressure, HRV, and glucose homeostasis were unaffected. Conclusions: Oily fish intake improved serum triacylglycerol and HDL cholesterol in a dose-dependent manner in 8- to 9-y-old children, but had no effect on blood pressure, HRV, or glucose homeostasis. This supports recommendations for fish intake in children and underlines the importance of initiatives to increase children's intake of oily fish. This trial was registered at clinicaltrials.gov as NCT02809508.